Effects of dietary n‐3 long‐chain polyunsaturated fatty acids (n‐3 LC‐PUFAs) on growth performance, body composition and subcutaneous adipose tissue transcriptome analysis of juvenile yellow drum (Nibea albiflora). (12th December 2020) - Tan, Peng; Wabike, Evelina E.; Qin, Gaochan; Lou, Bao; Xu, Dongdong; Chen, Ruiyi; Wang, Ligai
Abstract: Yellow drum juveniles were fed with graded n‐3 long‐chain polyunsaturated fatty acids (n‐3 LC‐PUFAs) diets (1.5–15.9 g/kg) for ten weeks. Fish growth performance was firstly promoted then inhibited by increased n‐3 LC‐PUFAs inclusion. The optimum n‐3 LC‐PUFAs were 9.0 g kg −1 and 9.5 g kg −1, referring to the weight gain rate and feed efficiency ratio, respectively. The increased n‐3 LC‐PUFAs inclusion significantly decreased ash and moisture content but increased crude lipid content ( p < .05). No significant alteration in fish protein content was observed among groups. Significantly higher saturated fatty acids proportion but the lower arachidonic acid proportion was observed in the subcutaneous adipose tissue (SCAT) of fish fed the diet with optimum n‐3 LC‐PUFAs group (9.8 g kg −1 ), compared with those of the control group (1.5 g kg −1 ) ( p < .05). Transcriptome analysis found differently expressed genes (DEGs) were mostly enriched in the peroxisome and fatty acid biosynthesis pathways. Besides, the expression of an immune‐related gene, Interleukin‐17D was observed to significantly changed ( p < .05). Therefore, 9.0–9.5 g kg −1 n‐3 LC‐PUFAs could be regarded as optimum for the yellow drum. Dietary n‐3 LC‐PUFAs affected the SCAT some metabolism and immunity genes expression.